QUANTITATIVE AND QUALITATIVE CHARACTERISTICS OF FIVE (5) ORIGINS OF MORINGA OLEIFERA FROM NIGER - Rabo Younoussou*; Abatcha Moustapha Yakaka*; Mahamane Ali** (Natural Resources and Sustainable Development, 2025)
Moringa oleifera is a leafy vegetable very rich in nutrients, highly valued by the Nigerien populations and of high socio-economic interest. This study, conducted in the commune of Diffa, aims at comparing the quantitative and qualitative characteristics of five (5) provenances of M. oleifera. Thus, an experimental Fisher block device was used and a total of five (5) treatments corresponding to the five (5) provenances of Diffa, Dosso, Maradi, Niamey and Zinder were used. In each experimental unit, four (4) M. oleifera plants were selected for observations. The study revealed the existence of 24 descriptors, of which fifteen (15) were quantitative and nine (9) were qualitative. Analysis of variance (ANOVA), Principal Component Analysis (PCA) and Hierarchical Ascending Classification (AHC) were performed. The results indicate significant variability between provenances. The G1 group consists of a single provenance, that of Diffa, which is early, and which’s length, width, height and number of branches are very important and gives a better yield in leaf weight per plant. The G2 group, made up of the 3 origins (Dosso, Maradi and Niamey), are intermediate to those of the other two groups. Then the G3 group made up of Zinder provenance which is more productive in dry biomass but not early. According to this study, it can therefore be conjectured that Diffa provenances can be proposed to the populations for an improvement in the leaf biomass production of M. oleifera.